PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PENDIDIKAN AGAMA ISLAM BERBASIS BOOK CREATOR - Kholis, Nur (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2024)
This study aims to produce interactive learning media for Islamic Religious Education based on Book Creator as an effort to improve learning outcomes for Islamic religious education courses. The development model used is the ADDIE model. There are three stages in the ADDIE development procedure, namely Analysis, Design and Develop. A limited trial was conducted on 10 students of the Health Polytechnic of the Ministry of Health of Riau to find out the respondents’ responses to the interactive learning media product for Islamic Religious Education based on Book Creator. The instrument used is a check list questionnaire. The results of the limited trial of student responses showed that the interactive learning media of Islamic Religious Education based on Book Creator had very good quality (86.76%) in addition to the overall assessment of reviewers and peer reviewers obtained very good quality (91.01%). Thus, it can be concluded that the Book Creator-based interactive learning media is appropriate to be used as a learning resource for Islamic Religious Education and can be used in learning activities. This article makes a positive contribution in the world of education, especially in the realm of utilizing digital platforms that can be used as learning media such as Book Creator.